A systematic review of loneliness and social isolation among Hispanic/Latinx older adults in the United States. (July 2022) - Tibiriçá, Lize; Jester, Dylan J.; Jeste, Dilip V.
Highlights: Examined the literature on loneliness and social isolation among older Hispanic/Latinx adults in the United States. There is no consistent difference in prevalence or severity of loneliness and social isolation between adults with different racial/ethnic backgrounds. There are differences in loneliness and social isolation among Hispanic/Latinx adults of different national origins. Suggestions for future research on loneliness and social isolation are discussed. Abstract: Loneliness and social isolation are growing public health problems in older adults, associated with physical and mental comorbidity and increased mortality. In the United States, Hispanic/Latinx individuals constitute the largest racial/ethnic minority. Studies retrieved from PsycInfo, Embase, and PubMed were examined. The initial search yielded 1476 publications. Using the updated PRISMA Flow guidelines, a total of 17 studies met our review criteria. Eight studies assessed loneliness, six evaluated social isolation, and three investigated both. The reports varied in the details of methodology, preventing meta-analyses. Differences in the experience of loneliness and social isolation between Hispanic/Latinx and White adults are not consistent. Of the three studies of loneliness or social isolation among Hispanic/Latinx groups of different national origins, two reported significant differences. Loneliness was associated with greater overall comorbidity, but two studies found higher risk of metabolic and cardiovascular disorders in Hispanic/Latinx with loneliness. Social isolation was generally associated with worse physical health, being older, male, and unmarried, and having lower education and income, and more smoking, along with frailty and cognitive impairment. We make specific suggestions for future research on loneliness and social isolation in Hispanic/Latinx adults and offer guidelines for clinical management.